Gangs - Stewart, Gail B. (Gail Barbara), 1949- (San Diego, Calif. : Greenhaven Press, 1998)
Presents contrasting viewpoints on the following questions: "How serious a problem are gangs in the United States?" "What factors encourage gang behavior?" and "How can gangs be eliminated?"
Includes bibliographical references (p. 104-107) and index.
Keywords: Gangs -- United States -- Juvenile literature; Gangs -- Government policy -- United States -- Juvenile literature; Violent crimes -- United States -- Juvenile literature; Crime prevention -- United States -- Juvenile literature; Gangs